Atmospheric Pollution in Chinese Cities: Trends and Persistence - Guglielmo Maria Caporale; Nieves Carmona-González; Luis Alberiko Gil-Alana (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper applies fractional integration methods to investigate the behaviour of various pollutants (PM10, PM25, SO2 and NO2) in seven Chinese cities (Shanghai, Beijing, Chongqing, Tianjin, Shenzhen, Nanjing and Xian) using daily data over the period January 1, 2014 – November 18, 2022. The results suggest that the steps recently taken by the Chinese authorities to reduce emissions and improve air quality have already had some effect: in most cases the air pollutant series are in the stationary range, with mean reversion occurring and shocks only having temporary effects, and there are significant downward trends indicating a decline over time in the degree of pollution in Chinese cities. It is also interesting that in the most recent period the Zero-Covid policy of the Chinese authorities has led to a further fall. On the whole, it would appear that the action plan adopted by the Chinese government is bringing the expected environmental benefits and therefore it is to be hoped that such policies will continue to be implemented and extended to improve air quality even further.
Keywords: C22; Q53; 330; China; pollution; trends; persistence; long-range dependence